2021
DOI: 10.3390/agriculture11121273
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation and Genome Mining of Bacillus subtilis Strain RS10 Reveals Its Biocontrol and Plant Growth-Promoting Potential

Abstract: Recently, crop management has involved excessive use of chemical fertilizers and pesticides, compromising public health and environmental integrity. Rhizobacteria, which can enhance plant growth and protect plants from phytopathogen, are eco-friendly and have been attracting increasing attention. In the current study, Bacillus subtilis RS10 isolated from the rhizosphere region of Cynodon dactylon, inhibited the growth of indicator strains and exhibited in vitro plant growth-promoting traits. A whole-genome ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…We also demonstrated that Q2H1 could solubilize organic phosphate in vitro. Similar to our results, other endophytes, such as Bacillus subtilis RS10 (Iqbal et al, 2021), E. roggenkampii ED5 (Guo et al, 2020), and B. subtilis EA-CB0575 (Franco-Sierra et al, 2020), have also been reported as phosphate solubilizers. Genes related to phosphate transport (pstACS) were found in the genome of B. subtilis strain RS10, which was confirmed in vitro and had favorable plant growth-promoting traits.…”
Section: Discussionsupporting
confidence: 91%
“…We also demonstrated that Q2H1 could solubilize organic phosphate in vitro. Similar to our results, other endophytes, such as Bacillus subtilis RS10 (Iqbal et al, 2021), E. roggenkampii ED5 (Guo et al, 2020), and B. subtilis EA-CB0575 (Franco-Sierra et al, 2020), have also been reported as phosphate solubilizers. Genes related to phosphate transport (pstACS) were found in the genome of B. subtilis strain RS10, which was confirmed in vitro and had favorable plant growth-promoting traits.…”
Section: Discussionsupporting
confidence: 91%
“…3 A, B). Of the eight known BGCs, four [terpenes, carotenoid, siderophore (staphylobactin), and bacillaene] have been well studied and were shown to be directly or indirectly implicated in PGP (Piccoli and Bottini 2013 ; Huang and Osbourn 2019 ; Bottini et al 2004 ; Fiodor et al 2021 ; Masunaka et al 2011 ; Salas-Marina et al 2011 ; Yuan et al 2015 ; Swapnil et al 2021 ; Sulochana et al 2014 ; Lurthy et al 2020 ; Iqbal et al 2021b ). These four BGCs were found between loci 2,036,992 and 2,054,897 bp (total 17,906 bp) for carotenoid, between 3,188,983 and 3,209,900 bp (20,918 bp) for cerecidin, between 904,761 and 925,605 bp (20,845 bp) for siderophore (staphylobactin), and between 537,059 and 626,796 bp (total 89,738 bp) for bacillaene.…”
Section: Resultsmentioning
confidence: 99%
“…Bacillaene is a polyene synthesized by trans-acyltransferase polyketide synthases via inhibition of prokaryotic protein biosynthesis. Furthermore, this compound has antibacterial activity, which indirectly promotes plant growth (Ji et al 2021 ; Chen et al 2019 ; Iqbal et al 2021b ). Additional research on these secondary metabolites is required to fully elucidate the functions of each metabolite in plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S can help plants resist various abiotic stresses such as drought, cold, heat, salinity, hypoxia, and toxic metals [ 47 ]. The cysCDHKMNZ gene, which is related to sulfate transport, was also identified in the CM253 genome [ 48 ]. Biofilm formation is the first step in root colonization by rhizosphere bacteria, which can help to mediate plant protection from environmental factors and plant diseases.…”
Section: Discussionmentioning
confidence: 99%